Jejunojejunal Intussusception as the Initial Presentation of Non-Hodgkin's B-Cell Lymphoma in an Adult Patient: A Case Report and Review of the Literature. (17th June 2013) - Stohlner, V.; Chatzizacharias, N. A.; Parthasarathy, M.; Groot-Wassink, T.
Abstract : Introduction . Intussusception is a rare cause of bowel obstruction in adults and is usually associated with an underlying pathology, benign, or malignant. This is a report of a case of jejunojejunal intussusception secondary to non-Hodgkin's B-cell lymphoma in an adult patient. Case Presentation . A 74-year-old male with no previous significant medical history presented with symptoms of acute intestinal obstruction. A CT scan of the abdomen and pelvis revealed 2 areas of jejunojejunal intussusception, which were surgically managed successfully. Histopathological examination of the specimen revealed the presence of high grade diffuse large B-cell-type non-Hodgkin's lymphoma, and the patient was referred to the oncology team for further management. Discussion . B-cell lymphoma is a rare but well-documented cause of intussusception in adults, with most cases being at the ileocolic region. We present a rare case of jejunojejunal intussusception as the initial presentation of non-Hodgkin's B-cell lymphoma in an adult patient.